Analysis of Employee Performance Evaluated Based on Key Performance Indicators (KPI) and Human Resources Scorecard (HRSC) PT Fastana Logistik Indonesia Divisi Transport - Amelia Khoerun Nisa; Enjang Suherman; Flora Patricia Anggela (Universitas Pamulang, 2023)
PT Fastana Logistik Indonesia (FLI) is a global supplier of transportation and logistics solutions. Performance measurement at PT Fastana Logistik Indonesia (FLI) uses KPI that aim to achieve company targets. PT Fastana Logistik Indonesia needs to evaluate not only with KPI but also with the HRSC method which emphasizes the human resource approach. This study aims to determine employee performance which is reviewed based on the Key Performance Indicator and Human Resources Scorecard. The research design uses a quantitative descriptive approach by collecting primary and secondary data from observations and questionnaires by measuring scores and interval scales. Quantitative data were then analyzed descriptively to draw conclusions. Based on the results of the study, it was shown that the performance of PT Fastana Logistik Indonesia in terms of the assessment of the Key Performance Indicator (KPI) and Human Resources Scorecard (HRSC) aspects obtained results if the Key Performance Indicator (KPI) obtained a score of 85.81% on very good/accomplished criteria, the results The Human Resources Scorecard (HRSC) obtained a score of 218 with percent 82,57% on a very good scale.